Pelatihan Digital Marketing untuk Meningkatkan Produktifitas Warga Padukuhan Trukan Sriharjo Imogiri Bantul Yogyakarta - Hidayatullah, Hidayatullah; Kusumaningtyas, Daru Putri; Yulianta, Eka; Siyamto, Yudi; Wibowo, Prihartanto Eko (Edumedia Solution, 2023)
In this community service discuss about marketing digital to increase productivity in society. So far, the world of marketing has only been known conventionally, with developments in the world of technology today, it is time for products to be marketed in a professional manner.digital or online. LPPM Yogyakarta Administrative Management Academy in collaboration with the Imogiri Bantul Yogyakarta sub-district government carried out community service centered in the Trukan Sriharjo Imogiri Bantul hamlet, Yogyakarta. The purpose of this community service is to provide digital marketing training to business actors in the community. From this program it was concluded that the Trukan Sriharjo Imogiri Bantul Yogyakarta community had practiced it digital marketing although there are still some players who market their business products conventionally in nearby markets. With this program, it adds to the knowledge of the community in the worlddigital marketng even though it is still simple in nature through the application whatapp. Obstacles in this community service program are the lack of socialization and limited facilities and infrastructure when this training is carried out.